(untitled) - Matz, Adolph (Ohio, 1962)
Contents: Cost accounting-managerial, conceptual, technical; Elements of cost; Process cost and estimated cost procedures; Budgetary control with standard costs;...
Keywords: Cost accounting,Phí tổn